Strategi Bisnis Umkm Untuk Naik Kelas Pasca Covid-19 - Syailendra, Siera; Setiawan, Mulkan; Sopian; Anggraini , Ria; Mustina Sari, Rahma (Universitas Indo Global Mandiri, 2024)
This research focuses on those who own MSME businesses, the economy during Covid-19 and strategies for MSME businesses to run again after Covid-19 by using online sales strategies. The aim of this research focuses on MSME business strategies to move up in class, the impact of developing MSME business strategies after Covid-19 and the effectiveness of MSME business strategies to move up in class. The conclusion of this research is that digital promotion and marketing is the right choice at this time because it is easy to reach and seen by many people, where online promotion can have a good image and impression and can influence many people. Apart from that, we still have to change the mindset of MSMEs so that they have a business mindset, not just a trading mindset. As a result, micro and small businesses face challenges when trying to advance into the medium sector due to their ingrained focus on trade-related activities, such as daily transactions. When operating in the micro, small, medium, or even large business field, entrepreneurs must shift their mindset from a narrow commerce focus to encompass broader aspects of business management. Their business mindset is limited to a limited scope. In contrast, medium-sized businesses operate with a comprehensive business mindset, which includes not only transaction management but also financial oversight, customer relations, systems management, and human resource management. Unlike MSMEs, medium-sized businesses with a business mindset go beyond routine activities, delving into advanced processes such as financial analysis beyond basic transactions. Apart from that, you also need to learn about E-Commerce, Digital Marketing, Product Service Improvement, and Customer Relationship Marketing (CRM) so you can do MSMEs using Online Media, Social Media, and Digital Marketing. Keywords: Business Strategy,UMKM, Upper Grade, Post Covid-19